2017
DOI: 10.2147/ott.s148604
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib, a MET inhibitor, inhibits growth, migration, and invasion of breast cancer cells in vitro and synergizes with chemotherapeutic agents

Abstract: MET is a receptor tyrosine kinase known for its pleiotropic effects in tumorigenesis. Dysregulations of MET expression and/or signaling have been reported and determined to be associated with inferior outcomes in breast cancer patients rendering MET a versatile candidate for targeted therapeutic intervention. Crizotinib is a multi-targeted small-molecule kinase inhibitor for MET, ALK, and ROS1 kinases. This study evaluated the anti-proliferative, cytotoxic, anti-migratory, and anti-invasive effects of crizotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Therefore, we investigated whether sacral and clival chordoma cells respond differently to a treatment with cMET inhibitors. The dual MET/ALK inhibitor crizotinib showed a dose-dependent reduction of viability in various breast cancer cell lines after 48 h of treatment, with an IC 50 of 5–10 µM 18 , which is similar to the IC 50 obtained in our HGF-stimulated, crizotinib-treated chordoma cells. Yakes et al tested the effect of cabozantinib, a small molecule tyrosine kinase inhibitor, on the proliferation behavior of different tumor cell lines and achieved different effects with respect to cMET amplification and IC 50 concentrations 19 .…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, we investigated whether sacral and clival chordoma cells respond differently to a treatment with cMET inhibitors. The dual MET/ALK inhibitor crizotinib showed a dose-dependent reduction of viability in various breast cancer cell lines after 48 h of treatment, with an IC 50 of 5–10 µM 18 , which is similar to the IC 50 obtained in our HGF-stimulated, crizotinib-treated chordoma cells. Yakes et al tested the effect of cabozantinib, a small molecule tyrosine kinase inhibitor, on the proliferation behavior of different tumor cell lines and achieved different effects with respect to cMET amplification and IC 50 concentrations 19 .…”
Section: Discussionsupporting
confidence: 80%
“…Our observations of dose‐dependent inhibition of HGF/R c‐MET phosphorylation by ICY‐5 in BC cells is therefore in line with previous literature, and resulted in the control of BC cell proliferation through the MET‐HGF axis. c‐MET activation plays a central role in BC progression (Ayoub, Al‐Shami, Alqudah, & Mhaidat, 2017). Previous studies showed that activated c‐MET promotes BC cell scattering, migration, and invasion following HGF ligand activation (Lawrence & Salgia, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib (or PF-02341066) is an ATP-competitive small-molecule inhibitor which blocks MET, anaplastic lymphoma receptor tyrosine kinase (ALK), c-ros oncogene 1 receptor tyrosine kinase (ROS1) and AXL. In breast cancer cell lines, it inhibits cellular proliferation [ 128 , 129 ]. As described for the other non-selective inhibitors, crizotinib is also involved in several clinical trials as a modulator of other molecular targets [ 22 ].…”
Section: Axl Inhibition In Breast Cancer Treatmentmentioning
confidence: 99%